Santità e agiografia al femminile Forme letterarie, tipologie e modelli nel mondo slavo orientale (X-XVII sec.) - FERRO, MARIA CHIARA (Biblioteca di Studi Slavistici, 2010)
The book comprises studies of twenty-four texts of Slavic-ecclesiastical production composed to recount the lives and celebrate the memory of eleven saints of the Russian Orthodox church who lived between the tenth and the seventeenth centuries: Ol'ga of Kiev (†969), Evfrosinija of Polock (†1173), Fevronija of Murom (†1228), Evfrosinija of Suzdal' (†1250), Anna of Kašin (XIII-XIV sec.), Sof'ja of Tver (XIII-XIV sec.), Vassa of Nižnij Novgorod (†1378), Julianija of Vjaz'ma (†1406), Evdokija of Moscow (†1407), Sof'ja of Suzdal' (†1542) and Julianija of Lazar'evo (†1604). Leaving to the historians the task of establishing the reliability of the hagiographic accounts handed down by the sources, the author intends to highlight the cultural influence of the texts in question. The analysis of the stylistic features, of the motifs and the bibliographical-liturgical citations contained in them, brings to light a characteristic profile of the female hagiography, identifying the image of the 'bride of Christ' as the model of sanctity for women. This interpretative key represents an initial approach to issues that have been addressed to date only in a superficial and sporadic manner as regards the East Slavic tradition, although they have begun to receive their due attention in the Latin and Byzantine sphere.